Needs Analysis of Digital-Based History Learning Resources in Senior High School - Santi Oktarina; Syarifuddin Syarifuddin; Siti Swasti Eka D (STAI Hubbulwathan Duri, 2023)
Contextualization of history learning can be done by utilizing the environment and phenomena, namely by using historical learning resources in the environment, one of which is a museum. However, the problem is that distance and time are not possible if the teacher takes the students to the museum location. An alternative solution for this learning period is the development of digital learning resources in the form of virtual museum tours for historical subjects. Before developing these learning resources, it is necessary to conduct an introduction to the main research on the development of historical learning resources. The purpose of this study was to determine the analysis of the needs and effectiveness of the Sriwijaya museum virtual tour as a digital history learning resource on learning outcomes in class X at a state senior high school in Palembang. The research method used is the mixed method with a qualitative approach and Classroom Action Research. The results of this study indicate that 71.8% of students are interested in simulating a visit to the Sriwijaya virtual museum via smartphones and that 100% of teachers need interactive learning resources and proven effectiveness in improving student learning outcomes to get an N-gain of 0.57 in the medium category.